Comparative Analysis of Guided Bone Regeneration and Allograft Materials in Periodontal Implant Treatment :A Systematic Review and Meta-Analysis - Waqas Memon; Mehvish Saleem; Ashfaque Ali Arain; Shazia Shaikh; Permanand; Arsalan Ahmed; Muhammad Hussain (Pakistan Journal of Medicine and Dentistry)
Background: Guided Bone Regeneration (GBR) treatment with allograft materials finds regular use in periodontal implant procedures to rebuild the alveolar bone structure and boost implant success rates. This systematic review and meta-analysis aimed to evaluate the effectiveness of GBR with allografts versus other implant approaches to identify the most effective periodontal treatment.